Impact of Dietary Advanced Glycation End-Product Restriction on Insulin Resistance and Anthropometric Indices in Coronary Artery Patients Treated with Percutaneous Coronary Intervention: A Randomized Controlled Trial - Elaheh Honarkar-Shafie; Mohammad Javad Hosseinzadeh-Attar; Fatemeh Taheri; Najme-Sadat Moosavi; Mehdi Yaseri; Mohammad Alidoosti; Ali Vasheghani-Farahani (Journal of Tehran University Heart Center, 2023)
Background: Insulin resistance (IR), even in its subclinical state, is a significant risk factor for the onset and progression of coronary artery disease (CAD). IR is a multifactorial condition, and dietary composition is a factor associated with its development. Elevated advanced glycation end products (AGEs) in the body, secondary to highly processed food consumption, can impair glucose metabolism. The present study investigated whether a restricted AGE diet could affect insulin sensitivity and anthropometric indices reflecting visceral adipose tissue in nondiabetic CAD patients.